Willingness and Hesitancy to Vaccinate Against COVID-19 in People with Multiple Sclerosis - Bučaitė, D.; Valinčiūtė, J.; Mickevičienė, D. (Neurologijos seminarai, 2023)
Introduction. During the pandemic, vaccination against COVID-19 has become one of the most important ways to prevent severe infection. However, a lack of trust in vaccines among the population, including people with multiple sclerosis (MS) has been identified. In Lithuania, the specific reasons for vaccine hesitancy among people with MS have not been described. We conducted a survey to determine the attitude of people with MS towards vaccination against COVID-19 infection.Methods. An original anonymous questionnaire was created. The survey included the following aspects: patient demographics, MS exacerbation, COVID-19 vaccination status, and attitudes towards the vaccination process. The survey was conducted between November 2021 and February 2022. Data were analyzed using IBM SPSS Statistics 27.0 with Chi-square and Mann-Whitney U tests and p-value (statistically significant at 0.05).Conclusion. Although there was some hesitancy about the COVID-19 vaccination, people with MS were more likely to take the COVID-19 vaccine due to their positive attitude towards the process.
Keywords: multiple sclerosis; COVID-19; vaccination